Filling in the voids of electrospun hydroxypropyl celulose network: dielectric investigations - MANAILA MAXIMEAN, DOINA (2018)
Here we describe an organic electro-optic device, obtained using electrospun hydroxypropyl cellulose (HPC) polymer fibres and nematic liquid crystals (LC). Its working mechanism is similar to that of a classic polymer-dispersed liquid crystal (PDLC) device. The scanning electron microscopy of the HPC deposited fibres shows a mat of fibres with diameters in the nano and micron size range. Dielectric spectroscopy measurements allow the determination of the dependence of the dielectric constant and electric energy loss on frequency and temperature as well as the determination of the activation energy. The electro-optic study shows a very good optical transmission curve, with an “on”-“off” switching voltage of less than 1V/μ m.